Molecular characterization of oxacillinases among carbapenem-resistant Acinetobacter baumannii nosocomial isolates in a Saudi hospital - Faten M. Elabd; Mohamed S.Z. Al-Ayed; Ahmed M. Asaad; Saeed A. Alsareii; Mohamed A. Qureshi; Hassan A.-A. Musa (Elsevier, 2015)
Summary: Background: Acinetobacter baumannii has successfully become a significant nosocomial pathogen because of its remarkable ability to acquire antibiotic resistance and to survive in nosocomial environments. This study aimed to determine the drug susceptibility patterns and the distribution of four subgroups of carbapenem-hydrolyzing class D β-lactamases (OXA-carbapenemases), as well as their insertion sequences (ISAba1), among A. baumannii nosocomial isolates from a Saudi tertiary care hospital. Methods: A total of 108 non-duplicate A. baumannii isolates were identified, and their susceptibilities to different antibiotics were determined using the breakpoint method. Isolates were then subjected to multiplex-PCR targeting blaOXA genes. Results: More than 75% of the isolates showed resistance to different antibiotics. The rates of susceptibility to colistin, meropenem, imipenem and trimethoprim-sulfamethoxazole were 95.6, 50, 48.1 and 34.3%, respectively. All isolates possessed a blaOXA-51-like gene. Of the 56 carbapenem-resistant isolates, 48 isolates (85.7%) carried blaOXA-23-like, 3 isolates (5.4%) carried blaOXA-40-like and two isolates (3.6%) had blaOXA-58-like genes. The ISAba1 element was found upstream of the blaOXA-23 and blaOXA-24 genes in 40 (71.4%) and 3 (5.4%) isolates, respectively, while it was detected upstream of blaOXA-51 in only one (1.8%) isolate. Conclusion: Our findings further illustrate the challenge of increasing carbapenem-resistance in A. baumannii isolates in Saudi Arabia. The high distribution of class D carbapenemase-encoding genes, mainly ISAba1/OXA-23 and ISAba1/OXA-24 carbapenemases, is worrisome and presents an emerging threat in our hospital. Local molecular surveillance is essential to help control carbapenem-resistant A. baumannii nosocomial infections and to prevent DNA exchange among endemic nosocomial pathogens. Keywords: Acinetobacter baumannii, Carbapenemases, Antibiotics, PCR